Mental health services for the deaf: an exploratory study of the aetiology, sources of information, and access to mental health services among deaf persons in Ghana - Maxwell Peprah Opoku; Wisdom Kwadwo Mprah; Juventus Duorinaah; Ebenezer Mensah Gyimah; William Nketsia; Lyla Adwan-Kamara (BMC, 2024)
Abstract Background The global burden of mental health disorders is on the increase, which has contributed to discussions on mitigation strategies. While mental health discourses in respect of access to services are still ongoing, there is limited focus on vulnerable groups. Deaf persons are at risk of exclusion from health services due to their unique modes of communication. In order to advocate for the inclusion of deaf persons in mental health services, there is a need for a study eliciting information on their knowledge about mental health and accessibility to services. Method The study was guided by a mixed-methods design and a two-phase data collection. In phase one, a questionnaire was distributed to 284 deaf persons to gather information on their knowledge of mental health conditions, causes, sources of information, and accessibility of services. Frequencies were used to report the trends identified in the data. Following this, an interview guide was designed based on the trends identified in the first phase to develop an in-depth insight into the experiences of deaf persons (n = 40) in respect of awareness and accessibility to mental health services. Results The results showed convergences and divergence between the qualitative and quantitative data. For instance, they were convergences between both datasets relative to knowledge on and causes of mental health conditions. Conclusion The study highlights the need for health policymakers to leverage the information gathered on the study participants' knowledge to develop appropriate mental health training programmes for deaf persons.